The first social project to popularize organ donation in Tatarstan based on the experience of the United States of America - A. A. Anisimov; E. S. Gilmetdinova; M. A. Mulendeeva; A. Yu. Anisimov (Трансплантология (Москва), 2022)
Relevance. The United States of America is currently one of the world leaders in organ donation and transplantation. In 2020, donor activity in the United States amounted to 38.0 per 1 million of the population, even exceeding the number in Spain 37.9 per 1 million of the population. In this context, the study of the American system of organ donation and transplantation in order to develop an accessible format for interaction with the population to strategically stimulate the potential of organ donation is of particular interest.Aim. To study the organ donation and transplantation system in Nebraska, United States of America, to develop an accessible format for interaction with the population to strategically stimulate the potential of organ donation in the Republic of Tatarstan.Material and methods. We presented the experience of the international internship «Organ donation and transplant management » at the University of Nebraska Medical Center (USA). We described the peculiarities of the functioning of the American transplant programs, the advantages in the matter of organizing organ and tissue donation.Results. In the USA, with a population of 327 million people, today more than 165 million (51%) people are registered as potential donors. At the end of 2018, in the United States 36,428 transplants of various organs and tissues, or 111.4 per 1 million population, were performed. At the same time, the number of deceased donors was 10,700, the number of living donors – 6,800. At the University of Nebraska Medical Center during the same period, 301 transplants (158.4 per million population) were performed from 68 deceased and 40 living donors. The analysis of the American system of organ donation and transplantation with effective interaction of the state, commercial and non-profit sectors, independent of the National Health System, made it possible to organize in 2020 the first social project in the Republic of Tatarstan on organ donation – "Donate Life Russia".Conclusion. The experience of the Republic of Tatarstan in attracting the non-profit sector to solving problems in the development of the transplant programs, following the example of the United States of America, has high potential in the Russian Federation.